2019
DOI: 10.3390/ijms20020320
|View full text |Cite
|
Sign up to set email alerts
|

c-Src Recruitment is Involved in c-MET-Mediated Malignant Behaviour of NT2D1 Non-Seminoma Cells

Abstract: c-MET pathway over-activation is the signature of malignancy acquisition or chemotherapy resistance of many cancers. We recently demonstrated that type II Testicular Germ Cell Tumours (TGCTs) express c-MET receptor. In particular, we elucidated that the non-seminoma lesions express c-MET protein at higher level, compared with the seminoma ones. In line with this observation, NTERA-2 clone D1 (NT2D1) non-seminoma cells increase their proliferation, migration and invasion in response to Hepatocyte Growth Factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 56 publications
(78 reference statements)
5
25
0
Order By: Relevance
“…Furthermore, the author found highest levels of c‐MET protein in non‐seminoma lesions compared with the GCNIS and seminoma samples (Scheri et al ., ). In a recent work, this research group has reported that inhibition of c‐Src resulted in abrogating HGF‐dependent NT2D1 cell proliferation, migration and invasion (Leonetti et al ., ). C‐Src, a proto‐oncogene, has been shown to be activated by c‐MET (Patel et al ., ), and this study indicates that c‐Scr is involved in c‐MET‐mediated malignancy in non‐seminoma.…”
Section: C‐met Signallingmentioning
confidence: 97%
“…Furthermore, the author found highest levels of c‐MET protein in non‐seminoma lesions compared with the GCNIS and seminoma samples (Scheri et al ., ). In a recent work, this research group has reported that inhibition of c‐Src resulted in abrogating HGF‐dependent NT2D1 cell proliferation, migration and invasion (Leonetti et al ., ). C‐Src, a proto‐oncogene, has been shown to be activated by c‐MET (Patel et al ., ), and this study indicates that c‐Scr is involved in c‐MET‐mediated malignancy in non‐seminoma.…”
Section: C‐met Signallingmentioning
confidence: 97%
“…Changes in the structure of nuclear compartment are frequently observed during transcription, cell differentiation, senescence, cell cycle and tumorigenesis [49], and evidence of active nuclear Src has been reported in different contexts. A study carried out on NT2D1 non-seminoma fibroblasts reveals that Src phosphorylation is constitutively present in the nuclei of these cells, representing a downstream effector of c-MET pathway [50]. c-MET is the membrane receptor of HGF (Hepatocyte Growth Factor).…”
Section: Regulation Of Gene Transcription and Chromatin Architecturementioning
confidence: 99%
“…c-MET recruits Src when activated by HGF, and this stimulus seems to be a key point allowing Src to translocate into the nucleus where it interacts with some gene promoters. In this context, a pivotal role is played by the cancer microenvironment, given that in the culture basal conditions (without administration of HGF) the inhibition of Src causes the augment of invasiveness but decreases the cell proliferation rate and migration capability of mouse NT2D1 fibroblasts independently from c-MET pathway, may be due to the Src recruitment by other homeostatic pathways controlling the aggressiveness of these cells [50].…”
Section: Regulation Of Gene Transcription and Chromatin Architecturementioning
confidence: 99%
“…We also demonstrated that c-Src inhibition abrogates the HGF-dependent increase of cell proliferation, polarized and collective migration, as well as cell invasion [ 9 ]. In the same paper, we found that, in basal culture conditions, c-Src inhibition decreases the cell proliferation rate of NT2D1 cells, independently from c-MET pathway activation, indicating that c-Src is used by other constitutively activated pathways that are responsible of activation of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In the same paper, we found that, in basal culture conditions, c-Src inhibition decreases the cell proliferation rate of NT2D1 cells, independently from c-MET pathway activation, indicating that c-Src is used by other constitutively activated pathways that are responsible of activation of the cell cycle. Notably, we also found that c-Src inhibition, when administered in basal culture conditions, increases NT2D1 invasiveness via a HGF-independent way, highlighting the importance of the microenvironmental cues in modulating cellular responses to pharmacological stimuli [ 9 ]. All together, these observations led us to further investigate the c-MET-triggered signal transduction pathway in non-seminoma cell malignant behavior.…”
Section: Introductionmentioning
confidence: 99%